Candle soot: onion-like carbon, an advanced anode material for a potassium-ion hybrid capacitor. Issue 15 (27th March 2019) - Chen, Jiangtao; Yang, Bingjun; Li, Hongxia; Ma, Pengjun; Lang, Junwei; Yan, Xingbin
Abstract : Onion-like carbon obtained from candle soot behaves as a high-performance anode for potassium-ion hybrid capacitors. Abstract : Although potassium-ion storage technology has started to receive significant attention, its development is still in its infancy; thus, exploration of suitable electrode materials is critical at this stage. Herein, onion-like carbon (OLC) was obtained from the combustion soot as the candle burnt and used as a promising anode material for potassium-ion storage. This OLC delivered high reversible capacity and exhibited good rate performance and cycling stability. Taking advantage of these features, a potassium-ion hybrid capacitor (PIHC) with OLC as the battery-type anode and activated carbon as the capacitor-type cathode was constructed. The constructed device displayed the high energy density of 142 W h kg −1, the ultrahigh power output of 21 kW kg −1, and a long cycling life (83% capacity retention after 6000 cycles). Thus, this device may simultaneously cater to the requirements of high power and high energy densities in a wide range of applications.